Research and Development – Commercialization Bridge: A Refined Model - Budi, Adi Asmariadi; Aldianto, Leo (The Asian Journal of Technology Management (AJTM), 2020)
Abstract. Research product commercialization becomes the problem in delivering research into commercialization. The objectives of this research are to understand research product commercialization, develop a framework, and generate a refined research product commercialization model. An in-depth interview method by purposive sampling was used to gather qualitative data. Interview transcriptions were analyzed through three steps networking processes. Those processes are proposed to generate a research product commercialization framework. The R&D flow and commercialization flow were developed based on that framework. A research product commercialization model was built through gaps and solutions arrangement on commercialization flow. Research and Development- Commercialization bridge (R&D-C Bridge) model was developed based on improved commercialization flow. R&D-C Institute, as an independent institute, runs that model. R&D-C institute also interconnecting stakeholders involved in the technology commercialization process that has already established on the technology park concept. While the Goldsmith and Stage-Gate commercialization model has un-clear tasks division and un-objective commercialization process, the R&D-C bridge model gives a research product commercialization flow through R&D-C institute as a stakeholder hub. It is where the R&D-C bridge model stands on its position. This research offers insights into developing a new research product commercialization model for science and technology park development.Keywords: A valley of death, commercialization constraints, commercialization model, research product, R&D-C bridge model